Bureau of Mines Respirable Dust Program: An Overview of Accomplishments and Future Research Plans - Robert A. Jankowski (The National Institute for Occupational Safety and Health (NIOSH), 1988)
"Following passage of the Coal Mine Health and Safety Act of 1969 (Public Law 911173), the Bureau of Mines initiated a research program aimed at controlling respirable dust exposures of coal mine workers. Respirable dust is the dust that gets into, and interacts with, the lungs of those who inhale it. It has long been recognized as a severe health hazard to mine workers. This program has been implemented by a team effort consisting of the Bureau's in-house capabilities, the Generic Center for Respirable Dust, and contractors, as necessary. Over the years, Bureau research has addressed principally three areas:o Compliance with the Federal 2.0 mg/m3 dust standard (1970-76).o Dust control for longwall mining (1976-1983).o More stringent respirable dust standards due to quartz dust (1983-1987).In addition, fundamental studies have been conducted by the Generic Center for Respirable Dust, with emphasis on penetration of dust into the lung. Accomplishments have been significant, but problems remain, as noted later.The Coal Mine Health and Safety Act of 1969, established a 2.0 mg/m3 dust standard for all coal mining operations, underground as well as surface. At the time of enactment of this legislation, the industry was averaging approximately 4.0 mg/m3. The Bureau of Mines respirable dust research program played a significant role in identifying and developing effective technology to allow better compliance with this new standard, thanks to industry implementation and Federal enforcement."